2023
DOI: 10.1101/2023.03.15.530972
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A test of the gleaner-opportunist trade-off among photosynthetic traits in Cryptophyte algae

Abstract: As photosynthetic producers, phytoplankton form the foundation of aquatic food webs. Understanding the relationships among photosynthetic traits in phytoplankton is essential to revealing how diversification of these traits allow phytoplankton to harvest energy from different light environments. We investigated whether the diversification of 15 species of cryptophytes, a phylum of phytoplankton with diverse light-capturing pigments, showed evidence of trade-offs among photosynthetic performance traits as predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…This somewhat narrow spatial scale relative to the dispersal capacity of duckweed (Coughlan et al, 2015;Les et al, 2003;Silva et al, 2018) It is also possible that we did not observe this trade-off because the Lemna species complex as a whole is not constrained by the gleaner-opportunist trade-off. For example, some work has shown that cryptophytes (a phylum of phytoplankton) are not constrained by this trade-off for photosynthetic light acquisition (Swanson et al, 2023). Additionally, a meta-analysis showed that the gleaneropportunist trade-off does not apply across taxa of heterotrophic eukaryotes (Kiørboe & Thomas, 2020).…”
Section: Gleaner-opportunist Trade-offsmentioning
confidence: 99%
“…This somewhat narrow spatial scale relative to the dispersal capacity of duckweed (Coughlan et al, 2015;Les et al, 2003;Silva et al, 2018) It is also possible that we did not observe this trade-off because the Lemna species complex as a whole is not constrained by the gleaner-opportunist trade-off. For example, some work has shown that cryptophytes (a phylum of phytoplankton) are not constrained by this trade-off for photosynthetic light acquisition (Swanson et al, 2023). Additionally, a meta-analysis showed that the gleaneropportunist trade-off does not apply across taxa of heterotrophic eukaryotes (Kiørboe & Thomas, 2020).…”
Section: Gleaner-opportunist Trade-offsmentioning
confidence: 99%
“…However, Senevirathna et al (2023) It is possible, however, that we did not observe this trade-off because the Lemna species complex as a whole is not constrained by the gleaner-opportunist trade-off. For example, some work has shown that cryptophytes (a phylum of phytoplankton) are not constrained by this trade-off for photosynthetic light acquisition (Swanson et al, 2023). Additionally, a meta-analysis showed that the gleaner-opportunist trade-off does not apply across taxa of heterotrophic eukaryotes (Kiørboe & Thomas, 2020).…”
Section: Gleaner-opportunist Trade-offsmentioning
confidence: 99%